2006
DOI: 10.1016/s1472-6483(10)61027-9
|View full text |Cite
|
Sign up to set email alerts
|

Successful pregnancy after ICSI with strontium oocyte activation in low rates of fertilization

Abstract: Fertilization failure (complete fertilization failure or low fertilization rates) after intracytoplasmic sperm injection (ICSI) can occur in rare cases. In the majority of these cases, the unfertilized oocytes are inactivated. Assisted oocyte activation was applied as a treatment option for a case of low fertilization rate as a clinical trial. A patient with a low fertilization rate (ranging from 0% to 33.3%; mean = 17.0%) after eight previous ICSI cycles at another hospital, was diagnosed with fertilization f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 32 publications
1
56
0
Order By: Relevance
“…Recently, several reports have demonstrated the efficacy of SrCl 2 after ICSI in couples who experienced complete fertilization failure or low fertilization rates in previous cycles of ICSI [17][18][19]. These results show that SrCl 2 treatment is useful for activating human oocytes that frequently fail to fertilize in ICSI.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Recently, several reports have demonstrated the efficacy of SrCl 2 after ICSI in couples who experienced complete fertilization failure or low fertilization rates in previous cycles of ICSI [17][18][19]. These results show that SrCl 2 treatment is useful for activating human oocytes that frequently fail to fertilize in ICSI.…”
Section: Discussionmentioning
confidence: 82%
“…When the oocytes were activated using electroporation [4,5], calcium ionophore [6][7][8][9][10][11][12][13][14], or calcium ionophore and puromycin [15,16], followed by ICSI in women whose oocytes failed to fertilize in previous IVF cycles, some of them could form pronuclei. Recently, several studies were reported that strontium chloride (SrCl 2 ) treatment on infertile patients resulted in successful pregnancies and deliveries [17][18][19]. Especially, SrCl 2 is excellent for improving fertilization, embryo quality, and pregnancy in women who showed complete fertilization failure or low fertilization rates.…”
Section: Introductionmentioning
confidence: 99%
“…Four case reports have been published demonstrating improved fertilisation rates and embryo quality following strontium was used for AOA in humans with low or no fertility, and successful pregnancies and live births have been achieved. [5][6][7] Our study is the first reported case of successful pregnancy and live births after strontium was used for AOA with globozoospermic sperm. However, the fertilisation rate was not improved after strontium treatment, even though it seemed to improve the quality of the embryos.…”
mentioning
confidence: 71%
“…3,4 Strontium treatment, which is proven to induce calcium oscillations in mice, was found to be an effective method for AOA in cases of low or absent fertilisation after ICSI. [5][6][7] Whether strontium is effective at improving fertilisation by globozoospermic sperm has not been reported. We report a successful case of a twin pregnancy resulting in live births following ICSI and strontium oocyte activation with round-headed sperm.…”
mentioning
confidence: 99%
See 1 more Smart Citation